The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1089/jir.2009.0105
|View full text |Cite
|
Sign up to set email alerts
|

Early Differential Expression of Oncostatin M in Obstructive Nephropathy

Abstract: Interstitial fibrosis plays a major role in progression of renal diseases. Oncostatin M (OSM) is a cytokine that regulates cell survival, differentiation, and proliferation. Renal tissue from patients with chronic obstructive nephropathy was examined for OSM expression. The elevated levels in diseased human kidneys suggested possible correlation between OSM level and kidney tissue fibrosis. Indeed, unilateral ureteral obstruction (UUO), a model of renal fibrosis, increased OSM and OSM receptor (OSM-R) expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
(16 reference statements)
0
19
0
Order By: Relevance
“…Consequently, it was revealed that OSMR gene silencing can obstruct the development of CAU by inhibiting the JAK/STAT3 signaling pathway, as increased proliferation, migration and decreased apoptosis of epithelial cells were observed in the OSMR-siRNA group. OSM, is a cytokine capable of modulating cell survival and proliferation, and the over-expression of OSM could result in transdifferentiation of epithelial-myofibroblast (Elbjeirami et al, 2010 ). In line with the findings of the current study, it was reported that over-expression of OSM in tubular epithelial cells might aggravate mucosal epithelial barrier dysfunction (Pothoven et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it was revealed that OSMR gene silencing can obstruct the development of CAU by inhibiting the JAK/STAT3 signaling pathway, as increased proliferation, migration and decreased apoptosis of epithelial cells were observed in the OSMR-siRNA group. OSM, is a cytokine capable of modulating cell survival and proliferation, and the over-expression of OSM could result in transdifferentiation of epithelial-myofibroblast (Elbjeirami et al, 2010 ). In line with the findings of the current study, it was reported that over-expression of OSM in tubular epithelial cells might aggravate mucosal epithelial barrier dysfunction (Pothoven et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…S3), all of which are associated with myofibroblast functions (Klingberg et al, 2013;Gerarduzzi and Di Battista, 2017). Furthermore, six out of the 20 most highly upregulated genes have been associated with myofibroblast activation, differentiation or function (Table 1, genes in bold) (Elbjeirami et al, 2010;Garrett et al, 2004;Gomez et al, 2016;Lenga et al, 2008;Lipson et al, 2012;Mifflin et al, 2002;Nightingale et al, 2004;Sobral et al, 2011). RT-qPCR analyses were performed for selected genes to confirm the microarray analyses (Fig.…”
Section: Loss Of Hippo Signaling Causes Müllerian Mesenchyme Cells Tmentioning
confidence: 97%
“…Although unilateral ureteral obstruction (UUO), a model of renal fibrogenesis, increased OSM and OSMR expression in a time‐dependent manner (Elbjeirami et al. ), we obtained evidence from preliminary microarray analysis of OSM‐stimulated human PTC that this IL‐6 family cytokine might also have antifibrotic effects (Pollack et al. ).…”
Section: Introductionmentioning
confidence: 85%
“…Chemokines such as CCL2 and their receptors are key mediators involved in inflammatory cell interactions and recruitment, cellular adhesion, differentiation, and tissue damage in the setting of diabetic nephropathy (Navarro-Gonz alez et al 2011 ;Kanasaki et al 2013;Wada and Makino 2013). Renal proximal tubular cells (PTC) represent important proinflammatory/profibrotic effector cells for OSM and several other proinflammatory/profibrotic ligands in these processes (Nightingale et al 2004;Pollack et al 2007;Elbjeirami et al 2010;Sark€ ozi et al 2011Sark€ ozi et al , 2012Tang and Lai 2012). Thus, we next studied mRNA expression of the chemokine CCL2 in human PTC selectively stimulated with IL-1b, TNF-a, or TGF-b1.…”
Section: Time-dependent Effects Of Il-1b Tnf-a Tgf-b1 and Osm On Cmentioning
confidence: 99%
See 1 more Smart Citation